Development Web Based 2D Education Game “Algo The Savior” - Muhammad Sultonul Hakim; Sumarno Sumarno (Procedia of Engineering and Life Science, 2022)
Basic programming is one of the most difficult learning subjects to learn because it requires skills in understanding the logic in a program, that's why teachers are required to use various alternative methods in learning about basic programming. One of the methods used is to use educational games. Based on these problems, the researcher intends to conduct research with the aim of making a basic programming educational game using Construct 2 application and the FSM (Finite State Machine) method, this game will be designed and created with the hope that this educational game that has been developed can provide convenience in learning basic programming subjects. The final result of this research is a prototype of an educational game entitled “Algo The Savior” which can be run with a web operating system.